The effects of interstitial hydrogen and carbon atoms and aging temperature on annihilation behavior of hydrogen-enhanced strain-induced vacancies in iron. (September 2021) - Sugiyama, Yuri; Kurihara, Nami; Matsumoto, Yuya; Takai, Kenichi
Abstract: The effects of interstitial hydrogen and carbon atoms and aging temperature on the annihilation behavior of hydrogen-enhanced strain-induced vacancies (HESIVs) in iron were examined using low-temperature thermal desorption spectroscopy (L-TDS) that can raise the temperature from −200 °C. Specimens containing HESIVs were aged under various conditions and charged with tracer hydrogen for detecting lattice defects. Atmospheric aging at 30 °C reduced small vacancies such as single vacancies and divacancies, which were thermally unstable, with increasing aging time, however, clustered vacancies remained after 7 days. In contrast, aging at −196 °C hardly caused any vacancy diffusion, aggregation, or annihilation. Aging in the presence of hydrogen and carbon at 30 °C reduced the rate of vacancy annihilation and left more vacancies, respectively. These findings indicate that interstitial hydrogen and carbon atoms in iron suppress the diffusion and annihilation of vacancies, resulting in vacancy stabilization. Graphical abstract: Tracer hydrogen spectra and amounts of tracer hydrogen of 6-ppm-C specimens containing vacancy-type defects and aged for various aging times (a) in the atmosphere at 30 °C, (b) with hydrogen charging at 30 °C and (c) in liquid nitrogen at −196 °C. Image, graphical abstract